A comparative study on the use of holmium laser and pneumatic lithotripser for intracorporeal lithotripsy of upper ureteric stones - Sharma, Elias; Langer, Raja; Dogra, Varun; Langer, Bhavna (International Surgery Journal, 2019)
Background: In the last decade different minimally invasive modalities for management of urolithiasis have been available requiring an intelligent decision by the urologist to choose one as per patients need and preferences. Methods: The present cross sectional study was conducted among patients who underwent ureterorenoscopic lithotripsy for proximal ureteric stones in the Department of Urology. Using consecutive sampling technique, patients were randomly allocated to two groups for treatment with either pneumatic lithotripser (group A) or Holmium laser lithotripser for fragmentation of calculi (group B) and the comparison of both these techniques was done. Results: 117 patients were included (57 and 60 in group A and group B respectively) in the study. The difference in age in the two groups was found to be statistically significant (p=0.03). The total operative time, length of stay in hospital and complications were more in group A patients. The difference in two groups for total operative time and length of stay in hospital was statistically significant (p=0.00 and 0.00 respectively). Conclusions: Holmium laser lithotripser has better safety profile when compared to pneumatic lithotripser especially in stone clearance rate and retropulsion rates and could be used as modality of choice in proximal ureteric stones.